2007
DOI: 10.1128/aac.00211-07
|View full text |Cite
|
Sign up to set email alerts
|

RSV604, a Novel Inhibitor of Respiratory Syncytial Virus Replication

Abstract: Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infections worldwide, yet no effective vaccine or antiviral treatment is available. Here we report the discovery and initial development of RSV604, a novel benzodiazepine with submicromolar anti-RSV activity. It proved to be equipotent against all clinical isolates tested of both the A and B subtypes of the virus. The compound has a low rate of in vitro resistance development. Sequencing revealed that the resistant virus had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 30 publications
4
78
0
3
Order By: Relevance
“…Several direct-acting, small-molecule inhibitors targeting different steps of the RSV life cycle were tested, including TMC-353121, an entry inhibitor targeting the RSV fusion protein (13); RSV-604, an early postentry inhibitor binding a conserved region of the nucleocapsid protein (14,15); YM-53403, an inhibitor targeting the RSV polymerase in variable region 2 (16); and BI-D, an inhibitor targeting the RSV polymerase in domain V (17). The mechanisms of inhibition by RSV-604 and YM-53403…”
mentioning
confidence: 99%
“…Several direct-acting, small-molecule inhibitors targeting different steps of the RSV life cycle were tested, including TMC-353121, an entry inhibitor targeting the RSV fusion protein (13); RSV-604, an early postentry inhibitor binding a conserved region of the nucleocapsid protein (14,15); YM-53403, an inhibitor targeting the RSV polymerase in variable region 2 (16); and BI-D, an inhibitor targeting the RSV polymerase in domain V (17). The mechanisms of inhibition by RSV-604 and YM-53403…”
mentioning
confidence: 99%
“…Two compounds with good antiviral potency were identified (compound 5: 50% inhibitory concentration [IC 50 ] ~110 nM; compound 6: IC 50 ~130 nM; Figure 3). Analogues of compound 5 displayed comparable potency (IC 50 46-74 nM). Detailed studies of the two lead compounds suggested that they interfered with viral fusion.…”
Section: Future Avenues Of Rsv Research)mentioning
confidence: 99%
“…Antiviral potency was returned to the template by combining this modification with C4 substitution to yield TMC353121 ( Figure 2). The compound had good activity against a range of RSV strains (50% effective concentrations [EC 50 ] 500 nM-30 pM) and a plasma half life between 4 and 24 h but still possessed a large volume of distribution (79 l) and poor oral availability. When dosed at 10 mg/kg in the cotton rat model it showed 0.4 log reduction of virus load orally and 1.2 log reduction via the intravenous route.…”
Section: Entry Including Fusion Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSV-604 (Arrow Therapeutics), an oral benzodiazepine with submicromolar potency against RSV A and B subfamilies (Chapman et al, 2007), is being developed in collaboration with Novartis. The safety and efficacy of this compound was tested in a multi-center trial that included RSV-infected adult bone marrow transplant patients.…”
Section: N-protein Inhibitorsmentioning
confidence: 99%